2017
DOI: 10.1016/j.tranon.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-489 Plays an Anti-Metastatic Role in Human Hepatocellular Carcinoma by Targeting Matrix Metalloproteinase-7

Abstract: Dysregulation of microRNAs (miRNAs) is actively involved in the pathogenesis and tumorigenicity of hepatocellular carcinoma (HCC). miR-489 was found to play either oncogenic or tumor suppressive roles in human cancers. Recent study reported that the levels of miR-489 in late recurrent HCC patients were evidently higher than that in early recurrent cases, suggesting that miR-489 may function as a tumor suppressive miRNA in HCC. Yet, the clinical value and biological function of miR-489 remain rarely known in HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Second, Lionel Remy et al reported that MMP7 promotes colon carcinoma cell migration via cleavage of the laminin-5 beta3 chain [13]. Additionally, MMP7 was reported as a target gene of the WNT/β-catenin signaling pathway in many carcinomas [39][40][41], and micro489 [42], state3 [14], and cox-2 [43] were reported as upstream genes of MMP7 in the cooperative function of regulatory carcinomas. Regrettably, the mechanism underlying how MMP7 promotes the proliferation, metastasis and invasion of tongue squamous cell carcinoma was not revealed, although we demonstrated that MMP7 acts as oncogene in TSCC, a finding that will push us to research further.…”
Section: Discussionmentioning
confidence: 99%
“…Second, Lionel Remy et al reported that MMP7 promotes colon carcinoma cell migration via cleavage of the laminin-5 beta3 chain [13]. Additionally, MMP7 was reported as a target gene of the WNT/β-catenin signaling pathway in many carcinomas [39][40][41], and micro489 [42], state3 [14], and cox-2 [43] were reported as upstream genes of MMP7 in the cooperative function of regulatory carcinomas. Regrettably, the mechanism underlying how MMP7 promotes the proliferation, metastasis and invasion of tongue squamous cell carcinoma was not revealed, although we demonstrated that MMP7 acts as oncogene in TSCC, a finding that will push us to research further.…”
Section: Discussionmentioning
confidence: 99%
“…27 In addition, miR-489-3p exhibits anti-metastatic activity in human hepatocellular carcinoma by targeting MMP7. 28 MiR-489-3p also inhibits growth and invasion by targeting HDAC7 in colorectal cancer. 29 Thus, miR-489-3p may exert antitumor activity via the regulation of not only DLX1 but also other oncogenes.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have been recognized as a new class of genes involved in human cancer and have recently been shown to be biomarkers of diagnostic, prognostic and therapeutic (10,11). Several studies have identified some miRNAs that were significantly altered and have the potential to restrain proliferation of cervical cancer (12,13).…”
Section: Introductionmentioning
confidence: 99%